Autobiography speech, a re-creator element to comics - Martoni, Bernard (Lumina - Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal de Juiz de Fora, 2015)
This paper proposes to relate autobiographical text to comics, in particular the graphic novel format. Traditionally comic books were usually related to humorous themes and a minor form of art, mainly because of a limited graphical technique due to the low quality of the printing process and this media origins which isassociated with American newspaper and European caricature, in both cases they do came from a non-traditional form of art or literature. During the history, comics development faces many changes concerning both thematic and artistic. In 1978, the cartoonist Will Eisner release the book A Contract with God: and Other Tenement Stories, considered for many as the first graphic novel and an important point in comics development in format and thematic sense. In 1975, Phillipe Lejeune presents the book The Autobiographical pact, in which he exposes his criteria to define a text as autobiographical. The proximity of those books’ release denotes an important aspect in this period, which provided a changing in many narrative medias, this autobiography element shows itself as a relevant aspect to understand comic’s production, particularly between 70’s and 80’s. In this sense, the present paper aims to identify the autobiography presence in comics and to show how it is affected by them. The presence of autobiography in comics shows themselves as a new possibility to explore this young media. It favored new possibilities in the medium, allowing a more personal and mature approach, a significant changing from super heroes thematic. To analyze this aspect, this work will focus on two important graphic novels: The Dreamer, by Will Eisner, and Maus: a survivor’s tale, by Art Spiegelman.